2015
DOI: 10.1136/oemed-2015-102992
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of workplace interventions in the prevention of upper extremity musculoskeletal disorders and symptoms: an update of the evidence

Abstract: The burden of disabling musculoskeletal pain and injuries (musculoskeletal disorders, MSDs) arising from work-related causes in many workplaces remains substantial. There is little consensus on the most appropriate interventions for MSDs. Our objective was to update a systematic review of workplace-based interventions for preventing and managing upper extremity MSD (UEMSD). We followed a systematic review process developed by the Institute for Work & Health and an adapted best evidence synthesis. 6 electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
196
0
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(228 citation statements)
references
References 100 publications
8
196
0
9
Order By: Relevance
“…The programme did not address all types of musculoskeletal disorders and we did not observe a reduction in other types of injuries. There are many other injury hazards within patient care units that can contribute to work-related injuries that may need other types of interventions;15 34 however, we did not see an increase in injuries and pain in these other areas, suggesting the programme did not shift the injuries to other regions of the body. Our patient handing practice outcomes were self-reported; however, there was a large increase in the use of slings, indicating that through the programme evaluation, there was a corresponding change in the demand for and use of slings associated with the use of mechanical lifts.…”
Section: Discussionmentioning
confidence: 55%
“…The programme did not address all types of musculoskeletal disorders and we did not observe a reduction in other types of injuries. There are many other injury hazards within patient care units that can contribute to work-related injuries that may need other types of interventions;15 34 however, we did not see an increase in injuries and pain in these other areas, suggesting the programme did not shift the injuries to other regions of the body. Our patient handing practice outcomes were self-reported; however, there was a large increase in the use of slings, indicating that through the programme evaluation, there was a corresponding change in the demand for and use of slings associated with the use of mechanical lifts.…”
Section: Discussionmentioning
confidence: 55%
“…The International Neck Pain Task Force (Hurwitz et al, 2008) and other systematic reviews have reported that exercises and manual therapy provide some degree of short-term relief of non-traumatic neck pain (Boocock et al, 2007;D'Sylva et al, 2010;. Active exercise is probably the single intervention that has the strongest scientific evidence for its clinical effectiveness (Andersen, Andersen, Zebis, & Sjøgaard, 2014;van Eerd et al, 2016;Viljanen et al, 2003;Waling, Järvholm, & Sundelin, 2002). Some recent studies have reported significant effects of resistance exercises in strengthening neck-shoulder musculature and reducing neck pain among office workers (Andersen et al, 2014;van Eerd et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Perceived fatigue was measured with 10 items altogether, referring to latent factors about lack of motivation, sleepiness, lack of energy, and physical exertion (26). The validity of the fatigue questionnaire was tested in the prior study (27).…”
Section: Methodsmentioning
confidence: 99%